Persuasive Strategies in Ustadz Abdul Somad’s Sermon on the Official YouTube Channel: An Aristotelian Rhetorical Analysis - Saddam Hakki; Rita Gamasari; Firgi Nurdianysah; Andi Putra (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
This study aims to analyze persuasive strategies in a sermon delivered through the YouTube account of Ustadz Abdul Somad using the Aristotelian rhetorical framework, which encompasses ethos, pathos, and logos. The object of analysis focuses on a sermon entitled “The Meaning and Wisdom of Commemorating the Birthday of Prophet Muhammad (PBUH)” broadcast on his official YouTube channel, which garnered 152,154 views, premiered on September 23, 2024, and has a duration of 1 hour, 5 minutes, and 48 seconds. This research employs a qualitative-descriptive approach using a case study method. Data were obtained from the sermon transcript and analyzed through content analysis techniques to identify forms of the preacher’s credibility (ethos), strategies for managing audience emotions through humor and narrative (pathos), and patterns of rational argumentation based on the Qur’an and Hadith (logos). The findings indicate that the effectiveness of his digital da’wah is constructed through a balanced integration of these three rhetorical elements, enabling religious messages to be conveyed in a persuasive, contextual, and rational manner to the audience, thereby affirming the relevance of Aristotelian rhetorical theory as an effective analytical framework for examining Islamic preaching in the era of digital media.